USM ACADEMIA FORWARDS RECOMMENDATIONS TO TACKLE FOREIGN IMMIGRANTS ISSUE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 27 May 2015 – The influx of foreign workers is an issue that is seen recently as becoming more critical, requiring a holistic approach that demands the involvement of many parties, including the academia. According to Dr. Shankar Chelliah, who lectures at the School of Management (SOM) in Universiti Sains Malaysia (USM) and chairs the International Business Programme, there are many factors contributing to the influx of foreign workers into the country.